Large‐Scale Integration of a Zinc Metasilicate Interface Layer Guiding Well‐Regulated Zn Deposition. Issue 27 (30th May 2022) - Guo, Ruiting; Liu, Xiong; Xia, Fanjie; Jiang, Yalong; Zhang, Huazhang; Huang, Meng; Niu, Chaojiang; Wu, Jinsong; Zhao, Yan; Wang, Xuanpeng; Han, Chunhua; Mai, Liqiang
Abstract: Uneven distribution of electric fields at the electrolyte–anode interface and associated Zn dendrite growth is one of the most critical barriers that limit the life span of aqueous zinc‐ion batteries. Herein, new‐type Zn–A–O (A = Si, Ti) interface layers with thin and uniform thickness, porosity, and hydrophilicity properties are developed to realize homogeneous and smooth Zn plating. For ZnSiO3 nanosheet arrays on Zn foil (Zn@ZSO), their formation follows an "etching–nucleation–growth" mechanism that is confirmed by a well‐designed Zn‐island‐based identical‐location microscopy method, the geometric area of which is up to 1000 cm 2 in one‐pot synthesis based on a low‐temperature wet‐chemical method. Guided by the structural advantages of the ZSO layer, the Zn 2+ flux gets equalized. Besides ultralow polarization, the life spans of symmetric cells and full cells coupled with a high‐mass‐loading K0.27 MnO2 ·0.54H2 O (8 mg cm −2 ) cathode, are increased by 3–7 times with the Zn@ZSO anode. Moreover, the large‐scale preparation of Zn@ZSO foil contributes to a 0.5 Ah multilayer pouch cell with high performance, further confirming its prospects for practical application. Abstract : A low‐temperature wet‐chemistry strategy with industrial operability is developed to realize large‐scale integration of Zn–Si–O nanosheet arrays on Zn foil. Zn‐island‐based identical‐location electron microscopy characterization is designed to visualize and uncover the in situ integration mechanism of Zn–Si–O layer. The life spans of symmetric cells, and full cells coupled with high‐mass‐loading cathode, have increased by 3–7 times.